The structure and properties of magnetic composites based on amorphous Fe alloys - Jeż, Bartłomiej; Postawa, Przemysław; Nabiałek, Marcin (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
Materials with so-called soft magnetic properties are an important object of material engineering research due to their potential application, among others, in the construction of low-loss transformer cores. Such properties are typical for alloys with an amorphous structure and with a high content of ferromagnetic elements: Fe, Co, Ni. Difficulties related with obtaining alloys which meet satisfactory dimensions result in the search for new solutions. One of them is the production of composites based on ferromagnetic powders obtained from amorphous alloys. This paper presents results of structure research for composite materials produced in a multi-stage production process. Magnetic composites were made on the basis of a bulk amorphous Fe70B20Y5Nb4Mo1 alloy produced by the injection method. On the basis of the obtained powder, two series of moldings were made: with 0.5% resin and covered with high-temperature varnish. Final composites were produced by using high temperature isostatic press. On the basis of the conducted research, it was found that the composites without resin are characterized by distinctly better magnetic properties as compared to resin-bonded composites.